Innovative strategies for reconstructing medical education through technology: a literature review - Li, Bingxue; Wu, Guodong; Shi, Linxi; Wang, Feng; Yang, Zhihong (Frontiers in Psychology, 2025)
Grounded in educational psychology, the landscape of medical education is experiencing a transformative evolution, catalyzed by the synergistic application of advanced technologies. This review synthesizes the burgeoning potential of neuroscientific research, big data analytics, mobile learning, virtual reality (VR), augmented reality (AR), social network analysis, natural language processing (NLP), physical activity monitoring, experimental economics, and adaptive learning technologies. These innovations are revolutionizing the educational paradigm by enabling personalized learning experiences, enhancing cognitive engagement, and fostering a collaborative ecosystem. The integration of these technologies not only promises to improve educational outcomes but also underscores the critical need for ethical stewardship and data privacy. As we navigate this new educational frontier, the prospects for nurturing a new generation of medical professionals are vast, with the potential to advance the quality and impact of healthcare delivery.